Sosialisasi Nilai Nasionalisme Dengan Menggunakan Modifikasi Role Playing Dan Answer Gallery di Karang Taruna Plosorejo - Kismantoro Kabupaten Wonogiri Tahun 2016 - Purnomo, Ugeng; , Dra. Sundari, SH.,M.Hum (2017)
This study aimed to describe describe the socialization of nationalism, challenges and solutions to overcome obstacles in the socialization of nationalism value using a modified Role Playing and Answers Gallery in Karangtaruna Plosorejo-Kismantoro Wonogiri 2016. The research is a qualitative descriptive. The subjects were young cadets coral, coral Taruna board, as well as the village head-Kismantoro Plosorejo Wonogiri 2016. This research object is the dissemination of nationalism value using a modified Role Playing and Answers Gallery in karang taruna Plosorejo-Kismantoro Wonogiri 2016. Techniques collecting data used in this study is an experiment, interview, observation and documentation. This study used two kinds of triangulation, the triangulation of data sources and triangulation techniques or methods of data collection. The results of the research are: 1) Orientation values of nationalism include: Role Playing and Answers Gallery is one method of learning is considered able to grow while enhancing the spirit of nationalism, socialization is done by playing a role or drama by taking the plot of a movie-themed battle entitled "General Sudirman". The steps in the socialization process using a modified Role Playing and Answers Gallery as follows: a) The first step is to introduce in advance to the members of the youth on the problems being faced is on the low values of nationalism that exists. b) After all understand the problems faced, the chairman of the youth and researchers choose a player that suits the character to be played. c) The head of the village, and the chairman of the youth to act as observers assist researchers in observing the implementation of role playing. d) The next step is the arrangement of the staging area. e) The next activity is starting to play a role with occasional diselipi debriefing as additional knowledge of the value of nationalism. f) During the role play progresses, one of the participants will provide the question cards placed on the table and a member or other players will look for the right answer. g) The final step is after the game is completed, the researcher and chairman of the youth accompanied by village provides clarification of material already played on the stage. 2) Obstacles encountered are: Obstacles found in the conduct of the socialization of nationalism by using a modification of the Role Playing and Answers Gallery among many members of the youth are still passive. 3) The solution to overcome obstacles in the socialization of the value of nationalism by using a modified model of Role Playing and Answers Gallery Youth Plosorejo- Kismantoro Wonogiri Regency in 2016 include: The solution obtained to overcome the obstacles in the implementation of the modification method and Answers Gallery Role Playing namely by pointing members of the passive youth to participate in the staging so that the members are not passive in the youth organization